The electronic nose in Lilliput. - Baltes, H. (IEEE spectrum)
Electronic noses today are handy enough systems for detecting gaseous chemicals used in industrial cleaning or fabrication processes. Available from a half-dozen manufacturers, the instruments are desktop or laptop in size, depending on their features. The gases, called volatile organic compounds (VOCs), are toxic, carcinogenic and quick to evaporate in combination, a danger to their environs. Here, the authors describe how a miniature experimental system based on a CMOS chip is being readied to detect a range of gaseous compounds